Cicero : 'haruspex' vicissitudinum mutationisque rei publicae : a study of Cicero's merit as political analyst - Schneider, Maridien (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2000.